Repercussões da hemodiálise na vida de mulheres - Bruna Eliane da Silva (2023)
This study focuses on the intersection of gender, daily life, and chronic kidney disease (CKD). The work justifies the research by pointing out the significant increase in CKD incidence among women and the need for a deeper understanding of the challenges they face. The text explores the effects of hemodialysis on the daily lives of women affected by CKD, emphasizing the importance of considering both gender and daily complexities when addressing health and wellbeing issues. The research adopted a qualitative approach, and for data collection, the Photovoice method was used. The study took place at a public university hospital in the interior of Minas Gerais, with women over 18 years of age receiving hemodialytic treatment. Data were collected through group sessions where participants' shared photos were presented and discussed based on guiding questions. Data analysis was conducted using the method of core meanings, with pre-indicators developed from repeated readings of collected texts and images. Relevant indicators were identified, and core meanings were then constructed considering each participant and their context. The sociodemographic results from the research suggest similarities with previous studies on chronic kidney disease, including age group, prevalence of conditions like systemic arterial hypertension (SAH), and diabetes mellitus (DM). Furthermore, it highlights significant transformations in the lives of participants due to chronic kidney disease, touching on various aspects such as leisure, caregiving, employment, and nutrition. The conclusions underscore the impact of gender and socioeconomic conditions on the experience of the disease and daily life changes in the participants' lives.